The importance of using tests to measure selection, guidance, and training requirements in the sports field - bachir, houssem; HAMLAOUI, Ameur (sports creativity, 2025)
High-level players frequently feel a strong desire to assess their abilities and skills in relation to the game's technical, physical, and tactical demands. Beginner players quickly develop a similar desire, especially since this allows them to understand their own level and progress. Despite this desire among players and the commitment of coaches, the reality is that the process of measuring and evaluating abilities, levels, and progress still requires greater attention, or at least needs to be properly implemented. The role of measurement and evaluation in the player selection process is growing, as it is considered the first step to success. This is in addition to what the correct test saves in terms of time, effort, and money with elements that do not promise future success in the game. Here, it should be noted that the role of measurement and evaluation in this regard does not stop at the initial selection process only, but this role continues throughout the stages of specialized performance and higher levels, by which we mean the stages of filtering or purification that follow the initial selection process. The way tests and measurements are conducted and the benefit of following them is an important factor to know the extent of progress in the level of motor performance, in addition to its benefit in making comparisons between groups of individuals or comparing the level of the same individual from time to time.